An interesting case of right ovarian cyst torsion: case report - Chavan, Niranjan N.; Bhutada, Radhika G.; Kapote, Deepali S.; C., Pushpa; Kampoowale, Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian torsion is a comparatively rare gynecological emergency. It commonly presents with complaints of acute abdominal pain, nausea, and vomiting. It occurs due to twisting of the ovarian pedicle leading to ischemic changes in the ovary. It can even result in complete loss of blood supply, eventually necrosis of the ovary. It is diagnosed clinically and can be confirmed on ultrasound color doppler. The management of ovarian torsion depends on the age of the patient, size of the mass, ovary condition, and USG findings. Early diagnosis and treatment of torsion are necessary to preserve the viability of the ovary. We are reporting a case of a 30-year-old female with right ovarian cyst torsion of size 6.3×6.8×6 cm. Once torsion is diagnosed surgery is the mainstay of treatment, either detorsion and ovariopexy or oophorectomy if the ovary cannot be salvaged.